BENTUK MAKAM-MAKAM BELANDA DI CILACAP DAN PURWOREJO - Muhammad Chawari (Berkala Arkeologi, 2003)
Dutch graves in Indonesia - especially Java, in Cilacap and Purworejo - have a distinctive shape. These forms are very different from the graves of the indigenous people in general. The difference is not only in the shape of the tomb, but also in size and variation. By studying the forms of the Dutch tombs, it can be seen the background of the differences in the shape of the tombs between one individual and another in Dutch society in Indonesia.